Kurikulum Pendidikan Islam Masa Klasik - Badriah, Laelatul (Literasi: Jurnal Ilmu Pendidikan, 2015)
Abstract Curriculum is a term that is very important for a good education lembaga Islamic educational institutions and public educational institutions. The curriculum covers all aspects related to the learning process. But studies curriculum more focus on four components, namely subject, goals, methods, and learning outcomes. Classical Islamic education curriculum can be regarded an Islamic education system beginning still very simple but of simplicity that is capable of scoring leaders, scholars, scientists lauar very unusual. Education applied Rosulullah in his time, he is the forerunner of Islamic education process that is capable of inspiration friends, Tabin, tabi’in tabi’in at this time. Education Rosulullah then forwarded by the first four Rasyidbani government period, then passed back to the Umayyads and the â€˜Abbasids Bani period. Where in each of the reign of Muslims is generally the same that emphasizes learning ketauhidan or divinity in order to establish the people Islam earlier. However curriculum that has not been well documented it can be inferred consists of learning materials, teaching methods, the subject of learning, learning outcomes and competence. Keywords: curriculum, classical period, education.